Kajian Hukum Penyelesaian Kasus Stateless di Indonesia (Studi Kasus di Kemenkumham Yogyakarta) - Anindita Salma Ramadhani; Armansyah Prasakti; T Heru Nurgiansah (CV. Rayyan Dwi Bharata, 2024)
Legal Study of Settlement of Stateless Cases in Indonesia (Case Study at the Yogyakarta Ministry of Law and Human Rights). Thesis. Yogyakarta. Faculty of Teacher Training and Education. PGRI University Yogyakarta. 2024. This research aims to find out about the legal study of resolving stateless cases in the Yogyakarta Ministry of Law and Human Rights. Data collection uses interviews, documentation, and observation techniques. The data analysis used is descriptive data analysis, which is data that is organized and interpreted so that the data can provide answers to problems that are the background to the problems in writing this thesis, and conclusions can be drawn. From the results of research on the resolution of stateless cases, it was found that children born to parents of different nationalities over the age of 18 (eighteen) years or already married and a maximum of 21 (twenty-one) years must have clear citizenship status by making an application by the provisions of the Law. Law Number 12 of 2006 concerning Citizenship and Government Regulation Number 21 of 2022 concerning Amendments to Government Regulation Number 2 of 2007 concerning Procedures for Obtaining, Losing, Cancelling, and Regaining Citizenship of the Republic of Indonesia was passed on May 31, 2022, and this regulation is only valid until 31 May 2024. Government Regulation Number 21 of 2022 is a form of legal protection and certainty for children resulting from mixed marriages